Deposisi Lapisan Tipis Polimer Hibrid TMSPMA:DCM dengan Teknik Spray-air Brush sebagai Bahan Luminesensi pada LWC-SSL Planar Beserta Karakteristik Optiknya - Annissa Aprilia; Norman Syakir; Hendro Hendro; Fitrilawati Fitrilawati (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2015)
Light wave coupling (LWC) approach in solid state lighting (SSL) planar is the one of method that offer an efficient in light distribution. In LWC system, optical wave guide plate is used in order to enhance light distribution which is integrated with LED lamp as an excitation source. PMMA based light guide plate (LGP) is used which is commonly utilized in flat panel display technology. This research introduce the thin film preparation of hybrid polymer TMSPMA (trimethoxysilylpropyl methacrylate) doped by organic chromophore DCM (4-(dicyanomethylene)-2-methyl-6-(4-dimethylaminostyryl-4H-pyran) via sol-gel route and deposited onto LGP as a substrate using spray-air brush technique. Poly-TMSPMA is used as a matrix to trap the molecules of organic phosphor to avoid it from color degradation. This thin film serves as material luminescence for color conversion from source led lamp as an excitation source. The results shows that spray-air brush technique is suitable for deposition in large area (>10 cm2) and effectively and efficiently compared with the other technique. Besides that, it is shown that the irradiance of luminescence thin film on optical wave guide substrate would be increase and produce a better apportionment light. Keywords: Solid State Lighting (SSL), Light Wave Coupling (LWC), TMSPMA, organic chromophore, spray-air brush.